2014
DOI: 10.1016/j.celrep.2014.08.035
|View full text |Cite
|
Sign up to set email alerts
|

NFATc1 Controls Skeletal Muscle Fiber Type and Is a Negative Regulator of MyoD Activity

Abstract: SUMMARY Skeletal muscle comprises a heterogeneous population of fibers with important physiological differences. Fast fibers are glycolytic and fatigue rapidly. Slow fibers utilize oxidative metabolism and are fatigue-resistant. Muscle diseases such as sarcopenia and atrophy selectively affect fast fibers, but the molecular mechanisms regulating fiber type-specific gene expression remain incompletely understood. Here, we show that the transcription factor NFATc1 controls fiber type composition and is required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 39 publications
4
76
0
Order By: Relevance
“…Therefore, the effect of Gα13 on NFATc1 appears to be quite distinct in skeletal muscle. This idea mirrors the reports that other isoforms except NFATc1 failed to determine fiber types in skeletal muscle (22,(38)(39)(40). We believe our research delineates the role of Gα13 signaling in the regulation of NFATc1 in energy homeostasis and elucidates the mechanism for how G protein signaling amplifies or blunts oxidative metabolism, thus providing insight into the NFATc1 regulatory pathway.…”
Section: 4 7 Jciorgsupporting
confidence: 56%
See 3 more Smart Citations
“…Therefore, the effect of Gα13 on NFATc1 appears to be quite distinct in skeletal muscle. This idea mirrors the reports that other isoforms except NFATc1 failed to determine fiber types in skeletal muscle (22,(38)(39)(40). We believe our research delineates the role of Gα13 signaling in the regulation of NFATc1 in energy homeostasis and elucidates the mechanism for how G protein signaling amplifies or blunts oxidative metabolism, thus providing insight into the NFATc1 regulatory pathway.…”
Section: 4 7 Jciorgsupporting
confidence: 56%
“…Thus, we propose that Gα13 may serve as a switch that controls the overall sensitivity of multiple receptors associated with energy metabolism. NFATc1 is the most studied regulator of myofiber type-associated gene expression (20)(21)(22). Our results reveal the physiological link between Gα13 and NFAT signaling both in vitro and in vivo.…”
Section: 4 7 Jciorgmentioning
confidence: 76%
See 2 more Smart Citations
“…Recent studies have shown that the expressions of MyHC I and MyHC IIa are regulated by the Ca 2+ /calcineurin/NFAT pathway (Emrani et al, ; Ravel‐Chapuis, Bélanger, Côté, Michel, & Jasmin, ) pacifically, and increase of the intracellular Ca 2+ leads to calcineurin activation and NFAT dephosphorylation consequently. The dephosphorylated NFAT will translocate to the promoter of the gene involved in oxidative metabolism in the nucleus to promote the transformation of glycolytic muscle fibres to oxidative muscle fibres in skeletal muscle (Ehlers, Celona, & Black, ; Lomonosova, Turtikova, & Shenkman, ; Pfluger et al, ). Recent studies have shown that thymol can also attenuate the oxidative stress and calcium uniporter malfunction to maintain mitochondrial function in rats (Nagoor Meeran, Jagadeesh, & Selvaraj, ) probably by regulating calcium homeostasis.…”
Section: Discussionmentioning
confidence: 99%